1999
DOI: 10.2165/00003088-199937020-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Valganciclovir and Ganciclovir Following Multiple Oral Dosages of Valganciclovir in HIV- and CMV-Seropositive Volunteers

Abstract: These results show that once daily oral valganciclovir can produce exposures of ganciclovir (AUC24) exceeding those attained using intravenous ganciclovir 10 mg/kg. This suggests that oral valganciclovir may be suitable in many circumstances currently requiring intravenous ganciclovir, allowing for more convenience in the management of patients with CMV retinitis by utilising a 2 or 4 tablet daily regimen to cover all phases of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(78 citation statements)
references
References 10 publications
2
75
1
Order By: Relevance
“…The AUC 24 values of GCV following dosing with VGC in this study (21.1 and 41.7 g ⅐ h/ml for the 450-and 900-mg doses, respectively) were higher than the AUC 24 values of 12.7 and 24.8 g ⅐ h/ml observed in HIV-infected individuals receiving doses of 450 and 875 mg, respectively (1,12). Evaluation of the pharmacokinetic parameters suggests that the difference is due to the longer terminal elimination t 1/2 (5.1 to 5.22 h) seen in the transplant recipients compared to that in HIV-infected patients (3.66 h).…”
Section: Discussioncontrasting
confidence: 70%
“…The AUC 24 values of GCV following dosing with VGC in this study (21.1 and 41.7 g ⅐ h/ml for the 450-and 900-mg doses, respectively) were higher than the AUC 24 values of 12.7 and 24.8 g ⅐ h/ml observed in HIV-infected individuals receiving doses of 450 and 875 mg, respectively (1,12). Evaluation of the pharmacokinetic parameters suggests that the difference is due to the longer terminal elimination t 1/2 (5.1 to 5.22 h) seen in the transplant recipients compared to that in HIV-infected patients (3.66 h).…”
Section: Discussioncontrasting
confidence: 70%
“…A drawback for ganciclovir is its low oral bioavailability, making intravenous administration necessary for most indications. Recently, the valyl ester valganciclovir (Valcyte) has become available as an oral prodrug, offering a ganciclovir exposure comparable to the intravenous formulation (45). It is currently indicated for the prevention of HCMV disease in certain subsets of transplant recipients.…”
Section: Ganciclovir and Acyclovirmentioning
confidence: 99%
“…Previous pharmacokinetic studies showed similar drug exposure to ganciclovir after a single oral dose of 900 mg valganciclovir as compared to an intravenous dose of 5 mg/kg ganciclovir. [9][10][11] Recently, oral valganciclovir and intravenous ganciclovir were shown to have similar efficacy in pre-emptive CMV treatment in solid organ transplant recipients. [12][13][14] As a consequence, the prevention of CMV disease in high-risk renal, renal-pancreas and heart transplant patients was added as another indication to the original approval of valganciclovir for the treatment of CMV retinitis in AIDS patients.…”
Section: Introductionmentioning
confidence: 99%